Serial S100B Sampling Detects Intracranial Lesion Development in Patients on Extracorporeal Membrane Oxygenation - Fletcher-Sandersjöö, Alexander; Lindblad, Caroline; Thelin, Eric Peter; Bartek Jr., Jiri; Sallisalmi, Marko; Elmi-Terander, Adrian; Svensson, Mikael; Bellander, Bo-Michael; Broman, Lars Mikael (Frontiers in Neurology, 2019)
Introduction: Intracranial lesion development is a recognized complication in adults treated with extracorporeal membrane oxygenation (ECMO) and is associated with increased mortality. As neurological assessment during ECMO treatment remains challenging, protein biomarkers of cerebral injury could provide an opportunity to detect intracranial lesion development at an early stage. The aim of this study was to determine if serially sampled S100B could be used to detect intracranial lesion development during ECMO treatment. Methods: We conducted an observational cohort study of all patients treated with ECMO at ECMO Center Karolinska (Karolinska University Hospital, Stockholm, Sweden) between January and August 2018, excluding patients who did not undergo a computerized tomography scan (CT) during treatment. S100B was prospectively collected at hospital admission and then once daily. The primary end-point was any type of CT verified intracranial lesion. Receiver operating characteristics (ROC) curves and Cox proportional hazards models were employed. Results: Twenty-nine patients were included, of which 15 (52%) developed an intracranial lesion and exhibited higher levels of S100B overall. S100B had a robust association with intracranial lesion development, especially during the first 200 hours following admission. The best area-under-curve (AUC) to predict intracranial lesion development was 40 and 140 hours following ECMO initiation, were a S100B level of 0.69μg/L had an AUC of 0.81 (0.628-0.997). S100B levels were markedly increased following the development of intracranial hemorrhage. Conclusions: Serial serum S100B samples in ECMO patients were both significantly elevated and had an increasing trajectory in patients developing intracranial lesions. Larger prospective trials are warranted to validate these findings and to ascertain their clinical utility.